LEXICAL AND GRAMMATICAL FEATURES OF THE INTERPRETATION OF AESOP’S FABLES IN CREATIVY UKRAINIAN WRITERS AND TRANSLATORS (ON THE MATERIAL OF TRANSLATIONS BY YURII MUSHAK) - Корольова, Наталія; Коробова , Богдана (Taras Shevchenko National University of Kyiv (Ukraine), 2021)
Ancient fable is one of the most notable phenomena of European literature. Many monuments of this genre are distinguished by high artistic skill and have not lost their aesthetic value to these days. Short stories with a moral component, the protagonists of which were the representatives of animate or inanimate nature, were known in ancient times. Aesop is considered the founder of fable’s genre, according to the legend he first made them in literary processing. The most commonly among the works of the ancient Greek fabulist there are the themes of hypocrisy and human recklessness, lies and greed, fame and its consequences. The traditional structure of fables usually has two components – a morality and a narrative, and its main elements are an instructive, figurative, concise presentation, the introduction to the plot of various species of animals, plants, natural phenomena, gods, etc., which endowed with traditional allegorical image. The events described in the fables have an instructive content, in which the negative social phenomena and the human traits are ridiculed with help of allegory. Each fable of the legendary master is a separate episode, not related to the rest of the fables. The article defines the concept of a fable, provides a theoretical justification for choosing the object of study, takes into account a state of the linguistic researches of a chosen topic, outlines the artistic features of the genre, determines a compositional, stylistic and speech structure of Aesop’s fables and their translations into Ukrainian. Yuri Mushak’s translations are distinguished by the desire to preserve the artistic features of Aesop’s fables with a detailed transfer of their individual linguistic and stylistic elements. At the same time, the translator manages to bring his translations closer to the living conditions and morals of the Ukrainian people, he widely uses abbreviations or, conversely, additions to the text, replacement, concretization, and so on. * One of the authors of the article is the member of the editorial board of the "Bulletin of Taras Shevchenko National University of Kyiv. Literary studies. Linguistics. Folklore Studies", and therefore they do not participate in the review and decision-making process regarding the publication of this article.

Антична байка – одне з найприкметніших явищ європейської літератури. Багато пам'яток цього жанру відрізняються високою художньою майстерністю та не втратили своєї естетичної цінності дотепер. Короткі оповідання з моральною складовою, діючими особами яких виступали представники живої або неживої природи, були відомі ще у стародавні часи. Основоположником жанру байки вважають легендарного Езопа, який, за легендою, уперше піддав їх літературній обробці. Найчастіше серед творів давньогрецького байкаря зустрічаються теми лицемірства й людської нерозсудливості, брехні й жадібності, слави та її наслідків. Традиційна структура байки передбачає зазвичай два компонента – мораль і оповідання, а її основними елементами є повчальність, фігуральність, стислість викладу, уведення до сюжету різних видів тварин, рослин, явищ природи, богів тощо, наділених традиційною алегоричністю образу. * Один з авторів статті є членом редакційної колегії «Вісника Київського національного університету імені Тараса Шевченка. Літературознавство. Мовознавство. Фольклористика», тому не брав участі у рецензуванні та прийнятті рішення щодо публікації цієї статті.
ЛЕКСИКО-ГРАМАТИЧНІ ОСОБЛИВОСТІ ІНТЕРПРЕТАЦІЇ БАЙОК ЕЗОПА У ТВОРЧОСТІ УКРАЇНСЬКИХ ПИСЬМЕННИКІВ-ПЕРЕКЛАДАЧІВ (НА МАТЕРІАЛІ ПЕРЕКЛАДІВ ЮРІЯ МУШАКА)
Keywords: ancient fable; Aesop; translation; lexical and grammatical features; антична байка; Езоп; переклад; лексико-граматичні особливості